2006
DOI: 10.1093/ndt/gfl436
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of anti-C1q antibodies in biopsy-proven active lupus nephritis

Abstract: Anti-C1q have a very high prevalence in biopsy-proven active lupus nephritis, thus a negative test result almost excludes active nephritis. The data support the hypothesis of a pathogenic role of anti-C1q in lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
137
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(153 citation statements)
references
References 24 publications
13
137
1
2
Order By: Relevance
“…Therefore, the absence of anti-C1q antibodies has been suggested as an indicator for excluding a diagnosis of lupus nephritis [Trendelenburg et al 1999[Trendelenburg et al , 2006. Significant correlations between anti-C1q titers and active lupus nephritis have also been reported [Akhter et al 2011;Moroni et al 2001;Trendelenburg et al 2006], with a sensitivity of 44-100% and a specificity of 70-92% reported by Moroni and colleagues [Moroni et al 2001]. Another study reported the detection of anti-C1q antibodies in SLE patients who did not have a history of renal disease but eventually developed lupus nephritis [Marto et al 2005].…”
Section: Antinucleosome Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the absence of anti-C1q antibodies has been suggested as an indicator for excluding a diagnosis of lupus nephritis [Trendelenburg et al 1999[Trendelenburg et al , 2006. Significant correlations between anti-C1q titers and active lupus nephritis have also been reported [Akhter et al 2011;Moroni et al 2001;Trendelenburg et al 2006], with a sensitivity of 44-100% and a specificity of 70-92% reported by Moroni and colleagues [Moroni et al 2001]. Another study reported the detection of anti-C1q antibodies in SLE patients who did not have a history of renal disease but eventually developed lupus nephritis [Marto et al 2005].…”
Section: Antinucleosome Antibodiesmentioning
confidence: 99%
“…Some investigators suggested that the prediction value would be further enhanced when both anti-C1q and anti-dsDNA were measured [Matrat et al 2011]. Moreover, it has been reported that levels of anti-C1q antibodies decreased after successful treatment of lupus nephritis [Trendelenburg et al 2006].…”
Section: Antinucleosome Antibodiesmentioning
confidence: 99%
“…9 Other biomarkers may reflect specific organ involvements, most notably lupus nephritis which is often mirrored by raised levels of autoantibodies against double-stranded (ds) DNA, nucleosomes and/or complement protein (C) 1q. 2,5,10 The Systemic Lupus International Collaborating Clinics/American College of Rheumatology damage index (SDI) 11 covers 12 organ systems and measures accumulated organ damage that has occurred since the onset of SLE. SDI is scored regardless of whether the damage can be attributed to SLE or to other causes.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble VCAM-1 (sVCAM-1) has been reported as a useful marker of adult SLE activity [9,10]. On the other hand, deficiency of the early classical pathway component C1q induces tissue damage [11,12] and the occurrence of autoantibodies to C1q in SLE has been shown to be associated with hypocomplementemia and severe active LN [13][14][15].…”
Section: Introductionmentioning
confidence: 99%